Children hospitalized with community-acquired pneumonia complicated by effusion: a single-centre retrospective cohort study - Gelila Alemayheu; Claire S. J. Lee; Laura K. Erdman; Jacqueline Wong; Candy Rutherford; Marek Smieja; Sarah Khan; Jeffrey M. Pernica (BMC, 2023)
Abstract Objectives To describe children hospitalized with community-acquired pneumonia complicated by effusion (cCAP). Design Retrospective cohort study. Setting A Canadian children's hospital. Participants Children without significant medical comorbidities aged < 18 years admitted from January 2015-December 2019 to either the Paediatric Medicine or Paediatric General Surgery services with any pneumonia discharge code who were documented to have an effusion/empyaema using ultrasound. Outcome measures Length of stay; admission to the paediatric intensive care unit; microbiologic diagnosis; antibiotic use. Results There were 109 children without significant medical comorbidities hospitalized for confirmed cCAP during the study period. Their median length of stay was 9 days (Q1-Q3 6-11 days) and 35/109 (32%) were admitted to the paediatric intensive care unit. Most (89/109, 74%) underwent procedural drainage. Length of stay was not associated with effusion size but was associated with time to drainage (0.60 days longer stay per day delay in drainage, 95%CI 0.19-1.0 days). Microbiologic diagnosis was more often made via molecular testing of pleural fluids (43/59, 73%) than via blood culture (12/109, 11%); the main aetiologic pathogens were S. pneumoniae (40/109, 37%), S. pyogenes (15/109, 14%), and S. aureus (7/109, 6%). Discharge on a narrow spectrum antibiotic (i.e. amoxicillin) was much more common when the cCAP pathogen was identified as compared to when it was not (68% vs. 24%, p < 0.001). Conclusions Children with cCAP were commonly hospitalized for prolonged periods. Prompt procedural drainage was associated with shorter hospital stays. Pleural fluid testing often facilitated microbiologic diagnosis, which itself was associated with more appropriate antibiotic therapy.